Familial Melanoma Associated with Li-Fraumeni Syndrome and Atypical Mole Syndrome: Total-body Digital Photography, Dermoscopy and Confocal Microscopy - Priscila Giavedoni; Marnie Ririe; Cristina Carrera; Susana Puig; Josep Malvehy (Medical Journals Sweden, 2017)
Li-Fraumeni syndrome (LFS) is a rare autosomal dominant disorder caused by a mutation in the p53 gene. Melanoma is considered to be a rare, controversial component of LFS. The aim of this study is to describe the utility of systematic screening for melanoma in patients with LFS and atypical mole syndrome. Two 28-year-old identical twin sisters with LFS and atypical moles were monitored by physical examination, total-body digital photography and dermoscopy between 2006 and 2014. A total of 117, predominantly dark-brown, reticular naevi were identified on case 1 and 105 on case 2. Excisions were performed during the evaluation period of 1 in-situ melanoma and 3 basal cell carcinomas in case 1, and 1 in-situ melanoma and 1 early invasive melanoma in case 2. The remaining melanocytic lesions in both patients were stable during follow-up. The 3 melanomas were new atypical lesions detected with total-body photography and dermoscopy. In conclusion, monitoring LFS patients with total-body photography and dermoscopy may be useful to detect early melanoma.